Formigas (Hymenoptera: Formicidae) e vespas parasitoides (Hymenoptera: Braconidae) em duas fitofisionomias de Cerrado - Iéck, Bianca da Cruz (Universidade Federal de São Carlos, 2022)
Environments with diversified vegetation in phytophysiognomies, such as the Cerrado, provide high species diversity. In the state of Minas Gerais, the cerrado occurs predominantly and has important conservation units to preserve the fauna and flora of this biome, with Serra da Canastra National Park (PNSC) standing out. Despite its extension and importance, studies on the biodiversity present in the park, especially on invertebrates, are still scarce. Thus, the present work aimed to know the fauna of ants and parasitoid wasps collected with Moericke traps in phytophysiognomies of rupestrian fields and gallery forest in Serra da Canastra National Park, MG, Brazil. For this, we used data collected monthly, from December 2018 to October 2019 at three collection points, each point represented by two adjacent areas: one of rocky field and one of gallery forest. A 50m transect was drawn in each area with 100 Moericke traps distributed, which were exposed for 48 hours. Data on parasitoid wasps were obtained at the subfamily level; ants were identified in morphospecies. A total of 11,143 ant specimens were collected, grouped into 96 morphospecies, belonging to 31 genera of 7 subfamilies, with 5,287 individuals recorded in the rocky field and 5,856 in the gallery forest. A total of 2,857 specimens of parasitoid wasps of the Braconidae family were collected, with 87 individuals found in rupestrian fields and 2,770 in gallery forest, distributed in 18 subfamilies. The ant species richness was significantly higher in the gallery forest and the composition was different in the gallery forest when compared to the rupestrian field. For parasitoid wasps there was a greater abundance of individuals in the gallery forest and a greater richness of subfamilies in the campo rupestre. This result can be explained by the vegetation structure, because in the gallery forest the number of diversified plant species forms a heterogeneous and complex environment, providing greater availability of food resources and nesting sites, allowing the occurrence of nests and the coexistence of a greater number of species. Considering that plant diversity can influence herbivore populations, the presence of endemic plants in the rupestrian fields may be able to harbor differentiated hosts of specialized parasitoid wasps. The results obtained in this work demonstrate that the Serra da Canastra National Park harbors a very rich fauna of ants and parasitoid wasps, with a high diversity of species, especially when considering the gallery forest. These results can be expanded from other studies to be carried out in the park area.
Ants (Hymenoptera: Formicidae) and parasitoid wasps (Hymenoptera: Braconidae) in two Cerrado phytophysiognomies
Keywords: Bioindicadores; Campo Rupestre; Mata de Galeria; Diversidade; Bioindicators; Rupestrian Field; Gallery Forest; Diversity; CIENCIAS BIOLOGICAS::ECOLOGIA